Effect of chitinase‐3‐like protein 1 on glucose metabolism: In vitro skeletal muscle and human genetic association study. Issue 10 (20th August 2020) - Kwak, So‐Young; Seo, Il Hyeok; Chung, InHyeok; Kim, Shin Ae; Lee, Jung Ok; Lee, Hye Jeong; Kim, Sung Eun; Han, Jeong Ah; Kang, Min Ju; Kim, Su Jin; Lim, Soo; Kim, Kyoung Min; et al.
Abstract: We investigated the effect of chitinase‐3‐like protein 1 (CHI3L1) on glucose metabolism and its underlying mechanisms in skeletal muscle cells, and evaluated whether the observed effects are relevant in humans. CHI3L1 was associated with increased glucose uptake in skeletal muscles in an AMP‐activated protein kinase (AMPK)‐dependent manner, and with increased intracellular calcium levels via PAR2. The improvement in glucose metabolism observed in an intraperitoneal glucose tolerance test on male C57BL/6J mice supported this association. Inhibition of the CaMKK was associated with suppression of CHI3L1‐mediated glucose uptake. Additionally, CHI3L1 was found to influence glucose uptake through the PI3K/AKT pathway. Results suggested that CHI3L1 stimulated the phosphorylation of AS160 and p38 MAPK downstream of AMPK and AKT, and the resultant GLUT4 translocation. In primary myoblast cells, stimulation of AMPK and AKT was observed in response to CHI3L1, underscoring the biological relevance of CHI3L1. CHI3L1 levels were elevated in cells under conditions that mimic exercise in vitro and in exercised mice in vivo, indicating that CHI3L1 is secreted during muscle contraction. Finally, similar associations between CHI3L1 and metabolic parameters were observed in humans alongside genotype associations between CHI3L1 and diabetes at the population level. CHI3L1 may be a potential therapeutic target for the treatment of diabetes.